Magic bunny dancing days - Bentley, Sue 1951-; Swan, Angela 1982- (London Penguin Group, 2010)
Sara is excited to perform in her dance recital, but when she sprains her ankle in rehearsal, dancing is out. But when Sara meets magical bunny Arrow, her dancing disaster turns into the perfect chance to meet a special friend.
"Puffin books."
Keywords: Rabbits -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Dance -- Juvenile fiction; Magic -- Fiction; Friendship -- Fiction; Children's stories